Implication of the RD(Rio)Mycobacterium tuberculosis sublineage in multidrug resistant tuberculosis in Portugal - David, S (2012)
Multidrug and extensively drug resistant Mycobacterium tuberculosis are a threat to tuberculosis control programs. Genotyping methods, such as spoligotyping and MIRU-VNTR typing (Mycobacterial Interspersed Repetitive Units), are useful in monitoring potentially epidemic strains and estimating strain phylogenetic lineages and/or genotypic families. M. tuberculosis Latin American Mediterranean (LAM) family is a major worldwide contributor to tuberculosis (TB). LAM specific molecular markers, Ag85C(103) single nucleotide polymorphism (SNP) and RD(Rio) long-sequence polymorphism (LSP), were used to characterize spoligotype signatures from 859 patient isolates from Portugal. LAM strains were found responsible for 57.7% of all tuberculosis cases. Strains with the RD(Rio) deletion (referred to as RD(Rio)) were estimated to represent 1/3 of all the strains and over 60% of the multidrug resistant (MDR) strains. The major spoligotype signature SIT20 belonging to the LAM1 RD(Rio) sublineage, represented close to 1/5th of all the strains, over 20% of which were MDR. Analysis of published datasets according to stipulated 12loci MIRU-VNTR RD(Rio) signatures revealed that 96.3% (129/134) of MDR and extensively drug resistant (XDR) clusters were RD(Rio). This is the first report associating the LAM RD(Rio) sublineage with MDR. These results are an important contribution to the monitoring of these strains with heightened transmission for future endeavors to arrest MDR-TB and XDR-TB.